HUBUNGAN ANTARA MOTIVASI IBU DALAM MELAKUKAN PIJAT BAYI DENGAN KENAIKAN BERAT BADAN BAYI - Oktaviani, Mega; Nababan, Tiarnida; Artika, Meina; Novrita, Nanda (STIKes William Booth Surabaya, 2025)
Background: Infant weight gain is an important sign of healthy growth and development. Various factors can influence infant weight, including nutritional intake, health conditions, and care received, including infant massage. Many mothers are motivated to provide infant massage in the hope that it can help support their infant's optimal growth. The purpose of this study was to determine the relationship between maternal motivation in performing infant massage and infant weight gain in Dusun VIII Suka Damai, Kwala Air Hitam Village, Selesai District, Langkat Regency. Methode: The research method used was quantitative research with a correlational analytical research design with a cross-sectional approach. The population in this study was 50 people. The sample in this study used the Slovin Formula so that the sample size was 33 respondents. The data collection method was by using a questionnaire that was prepared to measure the variables. The data analysis used was univariate analysis which was carried out descriptively on all existing variables and analysis using the Chi Square test. Result: The results showed that out of 33 respondents, 24 respondents (72.7%) experienced weight gain in their babies due to being massaged routinely and regularly. Discussion: The conclusion of this study is that there is a relationship between maternal motivation in performing infant massage and infant weight gain with a p value of 0.000. It is expected that educational institutions will always improve guidance and emphasis on materials on pediatric nursing, namely on maternal motivation in performing infant massage and infant weight gain